Palliative Fractionated Radiotherapy for Thoracic Non-Small Cell Lung Cancer: A Prospective Comparative Study - Khandelwal, Mayur; Sharma, Divya; Tawri, Priya; Paliwal, Shruti; Sharma, Neeti; Jakhar, Shankar Lal (Asian Pacific Journal of Cancer Care, 2024)
Background: Many patients with lung carcinoma present to the clinic with advanced disease and moderate to severe symptoms. Palliative radiotherapy (PTR) to the chest can alleviate symptoms related to intrathoracic pathology. The timing and fractionation schedule of PTR are critical for achieving symptomatic relief and response. Typically, the effects of radiotherapy become apparent within three months. This study aimed to investigate survival after PTR and evaluate symptomatic relief and adverse effects of different radiotherapy schedules. Methods: This prospective study included patients with non-small-cell lung cancer (NSCLC) who were scheduled to receive PTR between January 2022 and October 2022 at ATRCTRI Bikaner, Rajasthan. Data collected included pathology, tumor, node, and metastasis (TNM) classification of malignant tumors, stage, indication for PTR, starting date, radiotherapy schedule, completion status (yes/no), performance status (PS), and time of death. Results: Among 86 patients enrolled, 12 did not complete their radiotherapy course. The remaining 74 patients who received PTR were included in the analysis. Thirty patients (40%) died within 30 days of treatment, and 15 patients died within three months. Only 20 patients remained alive at six months. Symptomatic relief was observed more frequently with 20 Gy in 5 fractions. Survival was associated with PS 1-2 and 30 Gy/10 fractions. Dyspnea, hemoptysis, and superior vena cava (SVC) syndrome were the most common indications for PTR in this study. Almost all patients presented with more than one indication for PTR. The fractionated schedule of 30 Gy/10F was used more frequently in patients with good PS. Conclusion: This study shows that a significant number of patients who received PTR died before they could achieve the optimal effects of treatment. Performance status and histology were significant prognostic factors, with better outcomes observed in patients with PS 1-2 and squamous cell carcinoma. Based on our findings, we suggest that patients with PS 1-2 should be considered for fractionated PTR, while patients with PS ≥ 2 should be considered for shorter fractionation schedules or best supportive palliative care.